"Lie in the grass, the soft grass": Relaxation accounts of young children attending childcare. (February 2020) - Cooke, Emma; Thorpe, Karen; Clarke, Andrew; Houen, Sandy; Oakes, Candice; Staton, Sally
Highlights: Young children have sensory-rich conceptualisations and experiences of relaxation. Children's relaxation accounts contrast from the dominant medicalised discourses. Children must be afforded agency to choose where, when, and how they relax. Carers and educators should consult with children about relaxation preferences. Abstract: Relaxation is constructed as a health issue, often as a counter to stress. Such constructions serve to medicalise relaxation as a physiological or psychological treatment for stressful experiences. Yet, children's experiences and understandings of relaxation are not well documented and may differ from these prevailing adult conceptualisations. Situated within the sociology of childhood paradigm, this study investigated: How do young children attending childcare experience relaxation? Informed by a child-centric methodology, in 2018, we conducted drawing-prompted group interviews with 46 child participants aged three to five years old recruited from six childcare services in Brisbane, Australia. Children were asked about what it means to relax and what they did to relax. We found that children clearly articulated their relaxation experiences and conceptualised relaxation as sensory-rich experiences that centred on feelings of cosiness, comfortableness, and air temperature. Places and play were key to shaping children's relaxation experiences: common places for relaxation were in nature or at home, and various types of play were central. Recommendations for improving care practices include engaging children in conversations about their relaxation preferences, and affording children agency to choose experiences that are relaxing when in childcare settings.